Serviceability design charts for partially prestressed high-strength concrete girders - Shady Salem; Mohamed Abu-Krisha; Tarek Hassan; Tarek El-Hashimy (Scientific Reports, 2025)
Abstract This paper presents the development of serviceability-based design charts for partially prestressed high-strength concrete (HSC) girders, with a focus on cracking and deflection performance. Partially prestressed girders, which serve as an intermediate design between fully prestressed and conventionally reinforced concrete, offer both structural efficiency and economic benefits. However, there is a notable gap in research regarding specific serviceability guidelines, particularly for controlling cracking and deflection in these girders. To address this gap, this study utilizes validated finite element models to investigate key variables, including the concrete compressive strength, prestressing forces, and non-prestressed reinforcement ratios. Parametric investigation provides insights into the impact of these factors on girder behavior under service loads, leading to the development of practical design charts. These charts allow for quick estimation of the optimal prestressing and reinforcement ratios that meet predefined serviceability limits, simplifying the design process for engineers. The proposed charts offer an accessible, efficient tool for optimizing material usage while ensuring compliance with serviceability criteria, making them highly valuable for the design of HSC girders in bridges and other infrastructures. Ultimately, this research enhances the usability of partially prestressed HSC girders, promoting more effective and economical designs in structural engineering practice.